1990
DOI: 10.1111/j.1365-2222.1990.tb02772.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of allergic disease and IgE antibodies to house dust mite In schoolchildren in Taiwan

Abstract: The prevalence of positive specific IgE antibodies to house dust mites (Dermatophagoides pteronyssinus; D. farinae) was determined by enzyme-linked immunosorbent assay (ELISA) in 5097 (61%) volunteers of 8345 schoolchildren aged between 7 and 14 yr from two government schools. All of them filled out a questionnaire concerning allergic symptoms. Among them, 412 (8.1%) children showed a positive reaction to at least one of the two mite allergens, the range varying between 5.6 and 11.2% according to the child's a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…In the present study, total and Df-specific IgE levels were examined in children with asthma. Total levels of serum IgE were lower in preschool age asthmatic children than in school age children, as described in previous studies [11,12]. The Df-specific IgE-positive rates were lower in the infancy period than in the school age period.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, total and Df-specific IgE levels were examined in children with asthma. Total levels of serum IgE were lower in preschool age asthmatic children than in school age children, as described in previous studies [11,12]. The Df-specific IgE-positive rates were lower in the infancy period than in the school age period.…”
Section: Discussionsupporting
confidence: 84%
“…Such levels may be the outcome of the frequency of antigen exposure and may also increase naturally from infancy through school age [11]. Dermatophagoides farinae (Df ) is a mite for which specific IgE is found in more than 80% of school age children with asthma in Japan [12]. To study when children with asthma develop allergen-specific IgE and if anti-inflammatory medication affects IgE levels in cases of childhood asthma (wheezing) is of interest in devising optimal therapies.…”
Section: Introductionmentioning
confidence: 99%
“…4,[14][15][16] The influence of early childhood exposure to infections (the hygiene hypothesis), animals, and secondary tobacco smoke on the development of atopy and allergic rhinitis is still unknown. [17][18][19][20][21][22][23][24] Presentation of allergic rhinitis In childhood, allergic rhinitis is more frequent in boys, but in adults, it is more frequent in women.…”
Section: Executive Summary Definition Of Rhinitis [Summary Statement 1]mentioning
confidence: 99%
“…The growth of Dp is highest at 22-25°C temperatures and at relative humidity levels of 75-80%, typical of indoor conditions in Taiwan during August to November. Peak indoor Dp levels in Taiwan have been documented in August-November, declining in December through January, and to a trough in February [12,19], which coincides with the peaks and troughs of under-twos' hospitalizations. Clinical-immunological studies have also suggested that mite exposure is an important factor in pediatric asthma in Taiwan [18,19].…”
Section: Discussionmentioning
confidence: 90%